Konseptual Mengenai Tantangan Etika Akuntan Di Era Artificial Intelegence (AI) Di Indonesia Kajian Literatur - Sulistyawan, Fajar; Ajeng Tita Nawangsari (Indo Publishing, 2025)
This study analyzes the ethical challenges faced by accountants in Indonesia amid the rapid development of Artificial Intelligence (AI). AI has transformed accounting practices such as auditing, financial reporting, and fraud detection. Although it increases efficiency and accuracy, AI raises ethical issues including algorithmic bias, unclear accountability, data privacy risks, and excessive reliance on technology. This literature review synthesizes findings from national and international research to evaluate the relevance of the Indonesian Code of Ethics for Accountants and proposes recommendations to maintain professional integrity in the digital era.